On the origin of kinking in layered crystalline solids. (March 2021) - Plummer, G.; Rathod, H.; Srivastava, A.; Radovic, M.; Ouisse, T.; Yildizhan, M.; Persson, P.O.Å.; Lambrinou, K.; Barsoum, M.W.; Tucker, G.J.
Graphical abstract: Abstract: Kinking is a deformation mechanism ubiquitous to layered systems, ranging from the nanometer scale in layered crystalline solids, to the kilometer scale in geological formations. Herein, we demonstrate its origins in the former through multiscale experiments and atomistic simulations. When compressively loaded parallel to their basal planes, layered crystalline solids first buckle elastically, then nucleate atomic-scale, highly stressed ripplocation boundaries – a process driven by redistributing strain from energetically expensive in-plane bonds to cheaper out-of-plane bonds. The consequences are far reaching as the unique mechanical properties of layered crystalline solids are highly dependent upon their ability to deform by kinking. Moreover, the compressive strength of numerous natural and engineered layered systems depends upon the ease of kinking or lack there of.